Detection of Bartonellaspp. and Rickettsiaspp. in fleas, ticks and lice collected in rural areas of Peru - Cáceres, Abraham G. (2013)
Bartonellosis and rickettsiosis are commonly reported in Peru. In order to detect Bartonella sp. and Rickettsiasp. in fleas, ticks and lice, specimens from five distinct locations in Peru (Marizagua, Cajaruro, Jamalca, Lonya Grande and El Milagro) were collected and screened for the presence of these bacteria using PCR and later confirmation by DNA sequencing. The specimens collected were distributed in 102 pools (76 Ctenocephalides felis, 2 Ctenocephalides canis, 16 Pulex irritans, 5 Pediculus humanus, 2 Rhiphicephalus sanguineus, and 1 Boophilus spp.), where Bartonellawas detected in 17 pools (6 of C. felis, 9 of P. irritans, 1 of C. canis, and 1 P. humanus). Also, Rickettsiawas detected in 76 pools (62 C. felis, 10 P. irritans, 2 P. humanus, and 2 C. canis). Bartonella clarridgeiaewas detected in C. felis, C. canisand P. irritanspools at 5.3%, 50% and 12.5%, respectively.Bartonella rochalimaewas detected in one C. felisand two P. irritanspools at 1.3% and 12.5%, respectively. Furthermore, B. henselaewas detected in one C. felispool and one P. humanuspool corresponding to 1.3% and 20%, respectively; and Bartonella spp.was also found in 5 pools of P. irritansat 31.3%. Additionally, R. feliswas detected in C. felis, C. canisand P. irritanspools at 76.3%, 100% and 37.5%, respectively; and Rickettsia spp. was detected in C. felis, P. irritansand P. humanuspools at 5.3%, 25% and 40%, respectively. These results demonstrate the circulation of these bacteria in Peru.